2007
DOI: 10.1128/iai.00497-07
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of the Heme Binding Protein Gene Family of Bartonella quintana Is Accomplished by a Novel Promoter Element and Iron Response Regulator

Abstract: We previously identified a five-member family of hemin-binding proteins (Hbp's) of Bartonella quintana that bind hemin on the outer surface but share no homology with known bacterial heme receptors. Subsequently, we demonstrated that expression of the hbp family is significantly influenced by oxygen, heme, and temperature conditions encountered by the pathogen in the human host and the body louse vector; e.g., we observed a dramatic (>100-fold) increase in hbpC transcript levels in response to the "louse-like"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 70 publications
1
42
0
Order By: Relevance
“…Several iba autotransporters were confirmed to be upregulated during in vitro infections with B. henselae in a second study and were found to be essential for virulence in the two STM screens (e.g., Cfa) and immunogenic in infections (347,374,427,432). Furthermore, representatives of this group in B. quintana were shown to contain an H box in their promoters, which indicates regulation in response to the transcription factor Irr together with other virulencerelated genes, like those encoding the hemin binding proteins (26).…”
Section: Other Virulence Factorsmentioning
confidence: 81%
See 2 more Smart Citations
“…Several iba autotransporters were confirmed to be upregulated during in vitro infections with B. henselae in a second study and were found to be essential for virulence in the two STM screens (e.g., Cfa) and immunogenic in infections (347,374,427,432). Furthermore, representatives of this group in B. quintana were shown to contain an H box in their promoters, which indicates regulation in response to the transcription factor Irr together with other virulencerelated genes, like those encoding the hemin binding proteins (26).…”
Section: Other Virulence Factorsmentioning
confidence: 81%
“…Similarly, the filA gene just upstream of ctpA has also been suspected to encode a virulence factor, but no experimental findings that would confirm or discard this assumption have been published (293). It was, however, shown that the promoter of filA contains an H box that is indicative of transcriptional regulation by Irr together with other virulence factors such as the hemin binding proteins or OMP43 (26).…”
Section: Infection Of Erythrocytesmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the affinity of Irr for those DNA elements is very weak in vitro (21). In fact, in vitro binding studies of Irr from several organisms all require micromolar concentrations of protein to detect DNA binding (3,14,21,27). Herein, we show that Irr is a transcriptional repressor with high affinity for target DNA and that Irr occupies the promoters of target genes in vivo.…”
mentioning
confidence: 92%
“…However, genetic regulation of heme utilization and iron homeostasis in general differs substantially in the Alphaproteobacteria from that in Escherichia coli or other wellstudied model organisms. Whereas Fur is the primary global regulator of the iron stimulon in numerous bacterial species, this role is carried out by Irr, RirA, or both in the Alphaproteobacteria (3,5,6,11,23,27,28,30,34).…”
mentioning
confidence: 99%